THE APPROPRIACY OF DISCOURSE MARKERS USED IN PSYCHOLOGY DEPARTMENT STUDENTS’ CONVERSATIONS - Dina NovitaWijayanti; Fatmawati (Jurnal Pendidikan dan Kebudayaan Missio, 2019)
This study aims at investigatingthe types ofdiscourse markersused in Psychology department students’ conversations in Muria Kudus University based on the theory of discourse markers proposed by Schriffrin (1987). To shed a light on this topic, it is recommended to investigate the level of the appropriacy ofthe discourse markers used by the students. The study used descriptive qualitative approach in the form of discourse analysis. The researchers were interested in analyzing it because in some cases, when the students want to express their ideas in conversation, they unfortunately sometimes do not know how to respond to speaker’s question especially if they doubt or are confused what to say. There were 8 students who became the subjects of the study. They conducted the conversations in pairs for 20 minutes for each.The result of the research indicates that seven types discourse markers were identified in the students’ conversation, they were discourse marker and (47 times), discourse marker but (8 times), discourse marker because (7 times), discourse marker so (6 times), discourse markers oh (38 times), discourse markers you know (6 times), discourse markers I mean (2 times). The students did not use discourse marker now, then, well.For the level of appropriacy, the total number of92 discourse markers were usedappropriately and 22 were usedinappropriately.Therefore, it can be inferred that the level of appropriacy of discourse markers used in the conversations was high